OPTIMALISASI PRODUKSI DENGAN PEMANFAATAN OVEN PENGERING DAN PENGELOLAAN UMKM BREM (UMKM DI WONOGIRI) - Achmad Choerudin; Rahmatya Widyaswati (Jurnal Abdimas Bina Bangsa, 2022)
Often facing SMEs sector problems of the product quality, classical business marketing and sustainability. Based on the background continued should also increase the business processes and production of SMEs Brem in Wonogiri, Central Java, when rain that is productive and effective, improve the quality of management and strategies SMEs Brem marketing production manual still. The outcome of the activities it is (1) a dryer for increased productivity, (2) making management strategies by the manufacture, management module of SMEs financial planning and SMEs marketing, and (3) there should be greater product quality of various marketing management resources and the support of government